Rural finance and poverty alleviation - Zeller, Manfred; Sharma, Manohar (International Food Policy Research Institute, 1998)
The authors examine the lessons that rural financial institutions such as banks and cooperatives can learn from the informal lending sector. They also considers the roles government should play in the provision of financial services. The report’s findings are gleaned from a series of detailed household surveys conducted in nine countries of Asia and Africa: Bangladesh, Cameroon, China, Egypt, Ghana, Madagascar, Malawi, Nepal, and Pakistan. Most of the poor in these countries could benefit from credit, savings, and insurance services, but what is available varies greatly from country to country.